2019
DOI: 10.4155/fmc-2018-0522
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Oral Biofilms Using Visible Light and Water-Filtered Infrared a Radiation and Indocyanine Green

Abstract: Aim: To investigate the antimicrobial photodynamic therapy (aPDT) of visible light and water-filtered infrared A radiation in combination with indocyanine green (ICG) on planktonic oral microorganisms as well as on oral biofilm. Methods: The irradiation was conducted for 5 min in combination with ICG. Treatment with chlorhexidine served as a positive control. The number of colony forming units and bacterial vitality were quantified. Results: All tested bacterial strains and salivary bacteria were killed at a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Numerous studies have already reported high rates of reduction in viable microorganisms by aPDT of oral biofilms using VIS+wIRA in combination with photosensitizers such as toluidine blue (TB) and chlorine e6 (Ce6) [ 23 , 28 ]. Similar promising results regarding the number of surviving bacteria were also achieved in a recent study with the photosensitizer indocyanine green (ICG) [ 29 ]. This anionic photosensitizer is characterized by low toxicity, good tolerance and rare occurrence of side effects [ 30 ].…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Numerous studies have already reported high rates of reduction in viable microorganisms by aPDT of oral biofilms using VIS+wIRA in combination with photosensitizers such as toluidine blue (TB) and chlorine e6 (Ce6) [ 23 , 28 ]. Similar promising results regarding the number of surviving bacteria were also achieved in a recent study with the photosensitizer indocyanine green (ICG) [ 29 ]. This anionic photosensitizer is characterized by low toxicity, good tolerance and rare occurrence of side effects [ 30 ].…”
Section: Introductionsupporting
confidence: 72%
“…In contrast to the other studies with ICG, the biofilm examined was generated in situ on bovine enamel slabs and subjected to aPDT ex vivo. A previous study showed that VIS+wIRA in combination with ICG significantly reduced the number of planktonic bacteria within human saliva as well as the viable counts of oral microorganisms within initial adhesion and mature oral biofilms [ 29 ]. In the present study, the aim was to investigate whether aPDT with VIS+wIRA as the light source and ICG as the photosensitizer is able to change the diversity of living bacteria in the biofilm and to influence their microbial balance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the depth of penetration might be increased when compared to other photosensitizers. [25]. APDT with ICG has previously shown a significant antibacterial action against S. aureus, studied in the methicillin-resistant strains [26].…”
Section: Discussionmentioning
confidence: 99%